(untitled) (mathematica didactica, 2021)
A teacher should be able to assess the potential of student contributions from a mathematical point of view for developing rich and interconnected subject knowledge. This requires specific competencies that should be formed in such courses where seemingly unconnected areas of school mathematics are analyzed on the basis of central concepts of structural mathematics. Such courses will be understood, with reference to the theoretical concept of the fundamental idea, as a contribution to a professional mathematics educationin the teaching profession. This is concretized by means of possible course contents on the topic of „proportionality“.